Aplikasi Komputer Statistika dalam Pengelolaan Data Penelitian - Ferli Sitepu; Zahwa Aulya Putri; Muhammad Syarif Alfarizi; Dinul Khusnul Khaliq; Husna Hanifah; Agung Indrawan; Aldino Firmansyah; Dina Nurul Falah; Khairunnisa Aqila; Noval Satrio Ardana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The advancement of information technology has made a major contribution to the world of research, especially in data management and analysis. Statistical computer applications such as SPSS and Microsoft Excel are effective tools for analyzing data systematically, quickly, and accurately. This study aims to improve the role and effectiveness of the use of statistical computer applications in managing research data. By using a descriptive approach through literature studies and simple case studies, this study identifies the advantages, disadvantages, and challenges in using statistical software. The results of the study indicate that computer applications greatly assist researchers in the process of inputting, analyzing, and interpreting data. However, the effectiveness of its use also depends heavily on the level of statistical literacy and technological skills of the user. Training and assistance are needed so that the use of statistical computer applications can be optimized in research activities.